Perancangan Media Publikasi Kampung Seni Jelekong Bandung Jawa Barat - Kaniasari Rukmana, Nia (ATRAT: Jurnal Seni Rupa, 2025)
Jelekong Art Village in Bandung Regency, West Java, is a cultural destination known as a center for painting and traditional art. However, the potential of art and potential of art and culture in this area has not been fully recognized by the wider community due to the limited effective promotional media. This research aims to design a publication media that can increase the visibility of Kampung Seni Jelekong Art Village, as well as supporting the promotion of local art and culture potential to the community. The method used is a visual communication design approach with qualitative data analysis through interviews and observations to local communities, artists, and tourists. The results showed the need for publication media that is interactive and informative publication media, such as catalogs, brochures, posters. The media is designed with an aesthetic concept that aesthetic concept that is in accordance with the artistic and cultural identity of Jelekong Village. implementation of this publication media, it is hoped that the Jelekong Art Village can be more widely known widely, attract more visitors, and support the sustainability of local art and culture. local arts and culture. This research also contributes to development of design-based promotional strategies for other cultural tourism destinations.